Understanding and Managing Traumatic Brain Injury (TBI) in an Adult Male Prison - Mitchell, Tracey (Auckland University of Technology, 2019)
The prevalence of traumatic brain injury (TBI) in prison populations has been found to vary considerably. Prisoners who have experienced TBI are reported to be less likely to be able to comply with prison rules and complete a programme of rehabilitation as a result of persistent TBI-related symptoms. Trials of rehabilitation programmes for TBI-affected individuals have demonstrated success in the community, but there are no published studies within the prison context. This thesis comprises of two studies to answer the identified research question. Study one aimed to determine the prevalence of TBI in a prison population in New Zealand, and to identify whether age, ethnicity, offence type, security classification and sentence length were linked to TBI prevalence. Study two sought to understand whether a psychological intervention would improve symptoms, improve strategies for managing negative affect and decrease in-prison infractions. Further, participants’ experiences of the intervention were explored. In study one; all prisoners admitted to a new corrections facility over a 6-month period were screened for history of TBI. Of the 1061 eligible male prisoners, 1054 (99%) completed a TBI history screen. 672 (64%) had sustained at least one TBI in their lifetime, with 343 (32%) experiencing multiple injuries. A regression model was able to correctly classify 67% of cases, and revealed that being of Māori ethnicity or being imprisoned for violent, sexual or burglary offences were independently predictive of TBI (χ2 = 9.86, p= 0.28). In study two, a single centre Randomised Control Trial (RCT) pilot study was undertaken with 55 consenting prisoners utilising a manualised, combined, Cognitive Behavioural Therapy (CBT)/Mindfulness Based Stress Reduction (MBSR) intervention to facilitate coping for participants. Measures of post-concussion symptoms, negative affect repair and in-prison infractions were assessed at baseline, following the intervention and after twelve weeks. A thematic analysis was also conducted to understand the participants’ experience of TBI and the intervention/study process. The study found no statistical differences in the demographics between the intervention and wait list controls across the three time periods. There was reduction in the post-concussion symptoms, but no statistical differences between the groups were found across the three time periods. There were improvements in negative affect repair strategies for both groups, which were statistically significant for the intervention group following completion of the intervention, but this was not sustained at the twelve-week follow-up. Through the process of this thematic analysis, three main themes arose, namely: the journey into jail, the intervention and new understandings. With high TBI prevalence in prison and the risk of persistent problems, routine screening for TBI may help to identify prisoners at risk of persistent difficulties. A manualised TBI intervention has demonstrated improvement in self-management strategies within an adult male prison.
Keywords: Brain Injury; TBI; Prevalence; Mindfulness; Cognitive behavioural therapy; Prison; Prisoner; Offender